High-resolution extended source optical coherence tomography - Yu, Xiaojun (2016)
High resolution optical coherence tomography (OCT) is capable of providing detailed tissue microstructures that are critical for disease diagnosis, yet its sensitivity is usually degraded since the system key components are typically not working at their respective center wavelengths. We developed a novel imaging system that achieves enhanced sensitivity without axial resolution degradation by the use of a spectrally encoded extended source (SEES) technique; it allows larger sample power without exceeding the maximum permissible exposure (MPE). In this study, we demonstrate a high-resolution extended source (HRES) OCT system, which is capable of providing a transverse resolution of 4.4 µm and an axial resolution of 2.1 µm in air with the SEES technique. We first theoretically show a sensitivity advantage of 6-dB of the HRES-OCT over that of its point source counterpart using numerical simulations, and then experimentally validate the applicability of the SEES technique to high-resolution OCT (HR-OCT) by comparing the HRES-OCT with an equivalent point-source system. In the HRES-OCT system, a dispersive prism was placed in the infinity space of the sample arm optics to spectrally extend the visual angle (angular subtense) of the light source to 10.3 mrad. This extended source allowed ~4 times larger MPE than its point source counterpart, which results in an enhancement of ~6 dB in sensitivity. Specifically, to solve the unbalanced dispersion between the sample and the reference arm optics, we proposed easy and efficient methods for system calibration and dispersion correction, respectively. With a maximum scanning speed reaching up to 60K A-lines/s, we further conducted imaging experiments with HRES-OCT using the human fingertip in vivo and the swine eye tissues ex vivo. Results demonstrate that the HRES-OCT is able to achieve significantly larger penetration depth than its conventional point source OCT counterpart.